Amidine derivatives and Leishmania amazonensis: an evaluation of the effect of nitric oxide (NO) production on the parasite-macrophage interaction - Temporal, R. M. (2005)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Imunologia. Rio de Janeiro, RJ, Brasil.